Refusal in physical education—teachers’ strategies and utilization of digital media - Pierre Meinokat; Katja Reimers; Ingo Wagner (Frontiers in Sports and Active Living)
IntroductionPhysical education refusal (PER) is a subject-specific form of classroom disruption within physical education (PE). PE teachers are tasked with managing PER effectively to improve learning outcomes and protect their well-being. Teacher interventions occur across institutional, classroom, and relationship dimensions. However, existing research has not yet adequately addressed the increasing role of digitalization.MethodsTherefore, this interview study explores the potential of digital media by investigating PE teachers' strategies for dealing with PER (RQ1) and their use of digital media in this process (RQ2).ResultsFindings show, for the first time internationally, an empirical basis for connecting the dimensional framework to reported strategies, hereby confirming and enhancing existing research. Teachers tend to use strategies that are based in the classroom dimension where they seem to have the best possible influence. In terms of use of digital media, teachers prefer software solutions to deal with PER, supplemented, if possible and sensible, by hardware and methodical structuring.DiscussionCombining these findings into a preliminary model, this study lays the foundation for future research in dealing with PER in digitally based PE lessons.